Strain Theory Analysis on Wild Racing Cases in Indonesia: Legal and Criminological Aspect of Crime - Andini, Sekar Jagad Putri; Manullang, Claira Jennifer (The Indonesian Journal of International Clinical Legal Education, 2023)
This study delves into the application of strain criminology theory in the realm of wild racing, aiming to unravel the intricate dynamics that drive individuals to participate in this phenomenon. Strain theory posits that criminal behavior can emerge from the stress resulting from a disjunction between societal goals and available resources. In the context of street racing, this theory provides a lens through which to understand how individuals facing economic, social, or emotional pressures may find an outlet in engaging in illicit racing activities. Through a comprehensive secondary data analysis, incorporating case studies and relevant literature, this research endeavors to shed light on the role of strain criminology theory in the manifestation of wild racing. By examining various instances and drawing on existing knowledge, the study seeks to elucidate the underlying factors that contribute to the allure of street racing under conditions of strain. The ultimate goal is to deepen our understanding of the phenomenon and its implications for devising effective prevention strategies. The insights derived from this investigation hold significance not only in terms of academic understanding but also for practical applications in the field of law enforcement and social intervention. By grasping the nuanced interplay between strain and wild racing, policymakers and community leaders can develop targeted measures to alleviate the underlying stressors that may drive individuals towards engaging in this form of criminal behavior.